Investigation of Signaling Pathways of the G Protein-Coupled Receptors GPR55 and S1P1 - Carlred, Louise (My University, 2010)
GPR55 and S1P1 are two G protein-coupled receptors of high interest as pharmaceutical targets. GPR55, which previously has been denoted as an orphan receptor, has been found to bind to several cannabinoid ligands and might therefore belong to the cannabinoid receptor family. This family, which today consists of the receptors CB1 and CB2, have been shown to have a great impact on different biological functions, both physiological and pathophysiological. S1P1 is a sphingosine 1-phosphate (S1P) receptor that has been shown to have an impact on especially the cardiovascular and the immune system. Several agonists have been found to activate the receptors but the mechanism of action is still unclear since different studies have presented inconsisten findings. The aim of this study is therefore to investigate the signaling pathways of these receptors to get a deeper insight into the mechanism of action. To investigate the receptors, two main methods have been used; GTPγS assay and dynamic mass redistribution (DMR) assay by using Epic resonant waveguide grating (RWG) biosensor. A G-LISA quantification assay was also performed to investigate which proteins that are involved in the signaling pathway. To investigate if the proteins are Gαi coupled, pertussis toxin was used to inhibit this interaction. Other inhibitors against proteins in different signaling pathways were also used to explore the signal transduction. This study has confirmed that GPR55 is activated and inhibited by different cannabinoids, although there are other cannabinoids that have no effect on GPR55. S1P1 is primarily activated by the phospholipid S1P and the compounds SEW2871 and CYM5442. These findings were confirmed in both GPγS and DMR assay. Furthermore, S1P1 was found to couple to Gαi proteins whereas GPR55 did not interact with these proteins. It was also discovered that the mitogen-activated protein kinase (Erk) is an important actor in the signaling pathway of GPR55. Rac1, on the other hand, was not found to be activated in the quantification assay. This study has therefore provided some new clues about how the signal is transducted from the activated receptors into the cell.
Keywords: Industriell bioteknik; Industrial Biotechnology